Development of Diorama Based Learning Media to Improve Elementary School Students’ Creative Thinking Ability - Melinda, Wulan; Ariyani, Yusinta Dwi (DAS Institute, 2024)
Education is a crucial tool for fostering the progress and advancement of a nation. This study is supported by a theoretical framework that emphasizes the cognitive abilities and creative thinking skills of pupils in relation to the material ecology. The current outcomes have not yet reached their optimal state, mostly due to the ongoing learning process and the lack of appropriate implementation strategies. The utilization of media dioramas as an educational tool has been shown to enhance participants' creative thinking abilities in the context of science learning. Hence, the imperative is in the advancement of 3D diorama media as an internal tool for teacher support in facilitating learning, thereby enhancing students' creative thinking capabilities. The objective of this project is to investigate and design learning media in the form of dioramas, with the aim of enhancing critical thinking skills among fifth-grade students in elementary schools. This study employs a comprehensive literature review methodology to investigate the relationship between science learning, diorama media, and creative thinking ability. The results of this study based on the findings found that the utilization of dioramas as an alternative learning method by teachers has the potential to enhance students' creative thinking abilities during the learning process.